High-gloss high-surface-energy nylon composite material and preparation method and application thereof

CN122668535APending Publication Date: 2026-09-01NANJING JULONG SCIENCE & TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610924442.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

但是,上述方法普遍存在光泽度提升与表面能提高难以兼顾的缺陷:常规增亮剂主要通过润滑作用改善表面光洁度,但对材料表面能的贡献有限,而等离子、电晕等物理表面处理虽能暂时提高表面能,但效果不持久,且对材料本体光泽度无改善

Benefits of technology

(1)本发明提供的高光泽高表面能尼龙复合材料,添加分子链上引入马来酸酐极性基团的C9石油树脂,解决了非极性C9石油树脂与极性尼龙基体直接共混相容性差的问题。同时,MAH-g-C9中接枝的马来酸酐基团,使得材料的表面能增强至接近油墨,从而两者形成良好的润湿匹配。进一步地,通过润滑剂复配、玻璃微珠填充,与马来酸酐接枝C9石油树脂协同配合,实现尼龙材料光泽度和表面能的大幅提升,该尼龙材料无需预处理、可直接印刷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

This invention discloses a high-gloss, high-surface-energy nylon composite material, its preparation method, and its application, belonging to the field of engineering plastics technology. The nylon composite material, by mass fraction of raw materials, comprises: 45-75 parts nylon resin, 15-30 parts glass fiber, 5-15 parts maleic anhydride-grafted C9 petroleum resin, 0.5-2.3 parts composite lubricant, and 3-8 parts glass microspheres. The composite lubricant is selected from at least one of internal and external lubricants; the internal lubricant is selected from one or more of stearamide and ethylene bis-stearamide; and the external lubricant is selected from silicone powder. Grafting maleic anhydride groups into MAH-g-C9 enhances the surface energy of the material, resulting in good wetting matching between the two. Synergistically, the combination of lubricant and glass microsphere filling significantly improves the gloss and surface energy of the nylon material. This nylon material requires no pretreatment and can be directly printed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of engineering plastics technology, specifically relating to a high-gloss, high-surface-energy nylon composite material, its preparation method, and its application. Background Technology

[0002] Nylon (polyamide, PA) is an engineering plastic with excellent comprehensive properties. It has good mechanical properties, heat resistance, wear resistance and self-lubricating properties, and is widely used in electronics, machinery, automobiles, textiles and other fields.

[0003] When nylon materials are used in automotive interior components such as air vent blades and buttons, a high gloss is required. However, nylon materials, especially glass fiber reinforced nylon, have a relatively low gloss. Additionally, some functional buttons require printed text and icons, but nylon materials, due to their high crystallinity and dense surface, have a surface energy lower than that of ink, making printing difficult.

[0004] Currently, existing technologies include methods to improve the gloss of nylon materials by adding brightening agents and high-brightness masterbatches, as well as techniques to increase surface energy through physical treatments such as plasma and corona treatment. However, these methods generally suffer from the drawback of being unable to simultaneously improve gloss and surface energy: conventional brightening agents mainly improve surface smoothness through lubrication, but their contribution to the material's surface energy is limited; while physical surface treatments such as plasma and corona treatment can temporarily increase surface energy, the effect is not lasting and does not improve the material's intrinsic gloss.

[0005] Existing literature reports methods for modifying MC nylon with hydrogenated C9 petroleum resin to improve its toughness, as well as technical solutions for modifying recycled polyester / nylon / spandex blends with C5 / C9 copolymer petroleum resin to enhance mechanical properties. It is evident that current petroleum resin-modified nylon technologies aim to improve mechanical properties, but lack a systematic solution for simultaneously improving nylon gloss and surface energy to meet printing requirements. Summary of the Invention

[0006] To address the shortcomings of existing technologies, a high-gloss, high-surface-energy nylon composite material, its preparation method, and its applications are provided.

[0007] The objective of this invention is achieved through the following technical solution: In a first aspect, the present invention provides a high-gloss, high-surface-energy nylon composite material, comprising, by mass parts of raw materials: 45-75 parts nylon resin, 15-30 parts glass fiber, 5-15 parts maleic anhydride grafted C9 petroleum resin, 0.5-2.3 parts composite lubricant, and 3-8 parts glass microspheres. The composite lubricant is selected from at least one of internal lubricants and external lubricants; the internal lubricant is selected from one or more of stearamide and ethylene bis-stearamide; and the external lubricant is selected from silicone powder.

[0008] In some specific embodiments of the present invention, the high-gloss, high-surface-energy nylon composite material comprises, by mass parts of raw materials: 65-70 parts nylon resin, 25-30 parts glass fiber, 10-15 parts maleic anhydride-grafted C9 petroleum resin, 0.8-2.3 parts composite lubricant, and 3-6 parts glass microspheres. The composite lubricant consists of 0.3-0.8 parts stearamide and 0.5-1.5 parts silicone powder.

[0009] In some specific embodiments of the present invention, the maleic anhydride grafting rate of the maleic anhydride-grafted C9 petroleum resin is 1.5-3.5 wt%.

[0010] In some specific embodiments of the present invention, the method for preparing the maleic anhydride-grafted C9 petroleum resin includes, Maleic anhydride-grafted C9 petroleum resin was prepared by melt grafting C9 petroleum resin and maleic anhydride. The extrusion temperature for melt grafting is 160-230℃, and the amount of maleic anhydride added is 2-5 wt% of C9 petroleum resin based on the mass fraction of C9 petroleum resin.

[0011] In some specific embodiments of the present invention, the nylon resin is selected from one or more of PA6 resin and PA66 resin.

[0012] In some specific embodiments of the present invention, the average diameter of the glass fiber is 10-50 μm.

[0013] In some specific embodiments of the present invention, the glass microspheres are solid glass microspheres modified with silane coupling agents, with a particle size of 20-30 μm.

[0014] In some specific embodiments of the present invention, based on the mass fraction of the raw materials, 0.2-1 parts of other additives are also included, wherein the other additives are antioxidants.

[0015] Secondly, the present invention provides a method for preparing the high-gloss, high-surface-energy nylon composite material described in the first aspect, comprising, According to the above proportions, the other components except glass fiber are mixed in a high-temperature manner and fed into a twin-screw extruder through the main feed port. The glass fiber is fed into the twin-screw extruder through the side feed port. After melt blending, extrusion and pelletizing, a high-gloss high-surface-energy nylon composite material is obtained. The extrusion temperature is 240-280℃, and the screw speed is 280-300 rpm.

[0016] Thirdly, the present invention provides an application of the high-gloss, high-surface-energy nylon composite material described in the first aspect in the preparation of automotive interior parts, electronic product housings, and packaging containers.

[0017] The beneficial effects achieved by this invention are as follows: (1) The high-gloss, high-surface-energy nylon composite material provided by this invention incorporates C9 petroleum resin with maleic anhydride polar groups introduced into its molecular chain, solving the problem of poor compatibility between non-polar C9 petroleum resin and polar nylon matrix when directly blended. Simultaneously, the maleic anhydride groups grafted into MAH-g-C9 enhance the surface energy of the material to near that of ink, thus achieving good wetting matching between the two. Furthermore, through lubricant compounding and glass microsphere filling, in synergy with maleic anhydride-grafted C9 petroleum resin, a significant improvement in the gloss and surface energy of the nylon material is achieved. This nylon material requires no pretreatment and can be directly printed.

[0018] (2) The high gloss and high surface energy nylon composite material provided by the present invention, MAH-g-C9 improves the light scattering characteristics of the material, reduces surface micro defects, and the petroleum resin promotes the formation of a more regular surface morphology of the matrix resin during the molding process, thereby improving the gloss.

[0019] (3) The high-gloss, high-surface-energy nylon composite material provided by the present invention utilizes the partial structural similarity and good compatibility between C9 petroleum resin and various ink components to form an interface layer on the surface of the nylon material that has an affinity for ink, so that it can be printed directly without pretreatment. Detailed Implementation

[0020] The present invention will be further described in detail below with reference to specific embodiments. The following embodiments are not intended to limit the present invention, but only to illustrate the present invention. Unless otherwise specified, the experimental methods used in the following embodiments are generally performed under conventional conditions. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available.

[0021] The raw materials used in the embodiments and comparative examples of this invention are all commercially available, as shown in Table 1.

[0022] Table 1 Raw materials for high-gloss, high-surface-energy nylon composites

[0023] The preparation method of maleic anhydride-grafted C9 petroleum resin (MAH-g-C9) in this invention is as follows: C9 petroleum resin and maleic anhydride were added to a twin-screw extruder with a length-to-diameter ratio of 48:1 and melt-extruded at 160-200℃ to obtain maleic anhydride-grafted C9 petroleum resin; wherein, based on the mass fraction of C9 petroleum resin, the amount of maleic anhydride added was 3wt% of C9 petroleum resin.

[0024] The grafting rate of maleic anhydride-grafted C9 petroleum resin (MAH-g-C9) in this invention is determined by: measuring the anhydride content using acid-base titration (chemical titration) and then calculating the grafting rate using the following formula: Where V0 is the volume of alkali solution consumed in the titration of ungrafted C9 petroleum resin (mL); V1 is the volume of alkali solution consumed in the titration of purified grafted C9 petroleum resin (mL); C is the molar concentration of the standard alkali solution (mmol / mL); M is the molar mass of maleic anhydride, usually taken as 98 g / mol; and m is the mass of grafted C9 petroleum resin (g).

[0025] The methods for preparing nylon composite materials in the embodiments and comparative examples of the present invention are as follows: According to the component ratio of the examples or comparative examples, the components other than glass fiber are highly mixed and fed into a twin-screw extruder through the main feed port, while the glass fiber is fed into the twin-screw extruder through the side feed port, thereby avoiding excessive shearing and breakage. After melt blending, extrusion, and pelletizing, a nylon composite material is obtained; wherein, the extrusion temperature is 240-280℃ and the screw speed is 300 rpm.

[0026] The gloss of the nylon composite material in this invention is tested according to GB / T 8807-1988 "Test Method for Specular Gloss of Plastics" under a 60° incident angle, and the gloss data are obtained from the test on a smooth plate.

[0027] The surface energy of the nylon composite material in this invention is obtained by contact angle testing (Water / Diiodomethane) and calculated using the Owens-Wendt method.

[0028] The printing effect of the nylon composite material in this invention is evaluated with reference to GB / T 9286-1998 "Cross-cut test of paint and varnish film" (100-cross test), with grade 5B being the best.

[0029] Example 1 This embodiment provides a high-gloss, high-surface-energy nylon composite material, comprising, by mass fraction of raw materials: The mixture consists of 65 parts PA6 resin, 30 parts glass fiber (13 μm in diameter), 15 parts maleic anhydride-grafted C9 petroleum resin (MAH-g-C9), 0.8 parts stearamide, 1.5 parts silicone powder, 3 parts solid glass microspheres (KH560 surface-modified, with a particle size of 20-30 μm), and 0.2 parts antioxidant; wherein the antioxidant is obtained by mixing antioxidant 168 and antioxidant 1098 in a 1:1 mass ratio.

[0030] Example 2 This embodiment provides a high-gloss, high-surface-energy nylon composite material, comprising, by mass fraction of raw materials: The mixture consists of 70 parts PA6 resin, 30 parts glass fiber (13 μm in diameter), 10 parts maleic anhydride-grafted C9 petroleum resin (MAH-g-C9), 0.8 parts stearamide, 1 part silicone powder, 6 parts solid glass microspheres (KH560 surface-modified, with a particle size of 20-30 μm), and 0.2 parts antioxidant; wherein the antioxidant is obtained by mixing antioxidant 168 and antioxidant 1098 in a 1:1 mass ratio.

[0031] Example 3 This embodiment provides a high-gloss, high-surface-energy nylon composite material, comprising, by mass fraction of raw materials: 70 parts PA6 resin, 30 parts glass fiber (13μm in diameter), 10 parts maleic anhydride grafted C9 petroleum resin (MAH-g-C9), 0.8 parts stearamide, and 0.2 parts antioxidant; wherein the antioxidant is obtained by mixing antioxidant 168 and antioxidant 1098 in a 1:1 mass ratio.

[0032] Comparative Example 1 This comparative example provides a nylon composite material, comprising, by mass parts of raw materials: 70 parts PA6 resin, 30 parts glass fiber (13 μm in diameter), 0.8 parts stearamide, 6 parts solid glass microspheres (20-30 μm in particle size, treated with silane coupling agent), and 0.2 parts antioxidant; wherein the antioxidant is obtained by mixing antioxidant 168 and antioxidant 1098 in a 1:1 mass ratio.

[0033] Comparative Example 2 This comparative example provides a nylon composite material, comprising, by mass parts of raw materials: 70 parts PA6 resin, 30 parts glass fiber (13μm in diameter), 0.8 parts stearamide, 1.2 parts silicone powder, and 0.2 parts antioxidant; wherein the antioxidant is obtained by mixing antioxidant 168 and antioxidant 1098 in a 1:1 mass ratio.

[0034] Comparative Example 3 This comparative example provides a nylon composite material, comprising, by mass parts of raw materials: 70 parts PA6 resin, 30 parts glass fiber (13μm in diameter).

[0035] The formulation components of Examples 1-3 and Comparative Examples 1-2 are shown in Table 2.

[0036] Table 2. Formulation composition of Examples 1-3 and Comparative Examples 1-2

[0037] The gloss (60°, GU), surface energy, and the effect of direct printing without surface pretreatment of the nylon composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested and calculated. The results are shown in Table 3.

[0038] Table 3. Performance comparison of nylon composite materials in Examples 1-3 and Comparative Examples 1-2

[0039] Comparing Example 3 and Comparative Examples 1-3 in Table 3, it can be seen that the addition of MAH-g-C9 simultaneously improves gloss and surface energy. This is because, on the one hand, the maleic anhydride groups (-CO-O-CO-) grafted into MAH-g-C9 are polar groups, which can provide active sites with high surface energy on the material surface. After grafting modification, the surface polarity of the material is enhanced, and the surface energy increases from about 35-40 mN / m in ordinary nylon to 42-48 mN / m, forming a good wetting match with the surface tension of the ink (usually 36-50 mN / m). On the other hand, MAH-g-C9 has a high aromatic ring density and good optical transparency. Adding it to the nylon matrix can improve the light scattering characteristics of the material, reduce surface micro-defects, and the plasticity of petroleum resin can promote the formation of a more regular surface morphology of the matrix resin during molding, thereby improving gloss. Furthermore, by utilizing the partial structural similarity and good compatibility between C9 petroleum resin and various ink components, an interface layer with an affinity for ink is formed on the surface of the nylon material, allowing for direct printing without pretreatment. In other words, by introducing polar groups into the C9 petroleum resin molecular chain, the problem of poor compatibility between C9 petroleum resin and the nylon matrix is ​​solved. When MAH-g-C9 is blended as part of the nylon material, the interface layer formed on the material surface has a natural affinity with the ink components. The ink can more easily wet and adhere to the nylon surface, achieving good printing results without additional surface pretreatment. The effect of adding MAH-g-C9 cannot be achieved by simply compounding internal and external lubricants or adding glass microspheres alone.

[0040] Furthermore, as can be seen from Examples 1-3, the gloss and printability of the nylon material in Example 2 are significantly improved compared to Example 3, while still maintaining a high surface energy. This is due to the synergistic effect of MAH-g-C9, the compounded lubricant, and the glass microspheres. Based on the MAH-g-C9 system's ability to regulate the surface chemical properties of the material at the molecular level, provide high surface energy active sites, and improve ink wettability, the lubricant compound and glass microsphere filling improve surface smoothness at the physical level, achieving a synergistic effect of physical-chemical dual modification. Specifically, in the lubricant compound system, the internal lubricant reduces the friction between polymer molecular chains and improves melt flowability, while the external lubricant acts as an isolation and lubricant at the mold-melt interface, reducing demolding resistance and resulting in a smooth and glossy product surface. Both work synergistically to improve surface smoothness at the macroscopic level, while the glass microsphere filling system further fills surface defects at the microscopic level and improves gloss through the "ball effect."

[0041] Furthermore, under the formulation of Example 1, the nylon composite material exhibits the best gloss (60°, GU), surface energy, and printing effect without surface pretreatment. The synergistic effect of these three factors significantly enhances the gloss and surface energy of the material, achieving 5B-level printing adhesion without pretreatment.

[0042] In summary, the high-gloss, high-surface-energy nylon composite material provided by this invention is the first to utilize maleic anhydride-grafted C9 petroleum resin to simultaneously improve the gloss and surface energy of nylon, solving the problem of the difficulty in achieving both simultaneously. By enhancing surface energy and ink affinity through the MAH-g-C9 polar groups at a chemical level, combined with the physical level of improving smoothness and gloss through lubricant formulation and glass microspheres, a dual physical-chemical synergy significantly improves the gloss and surface energy of nylon. Furthermore, it allows for direct printing without pretreatment such as plasma or corona treatment, simplifying the process and reducing costs.

[0043] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A high-gloss, high-surface-energy nylon composite material, characterized in that: Based on the mass fractions of raw materials, it includes: 45-75 parts nylon resin, 15-30 parts glass fiber, 5-15 parts maleic anhydride grafted C9 petroleum resin, 0.5-2.3 parts composite lubricant, and 3-8 parts glass microspheres. The composite lubricant is selected from at least one of internal lubricants and external lubricants; the internal lubricant is selected from one or more of stearamide and ethylene bis-stearamide; and the external lubricant is selected from silicone powder.

2. The high-gloss, high-surface-energy nylon composite material according to claim 1, characterized in that: Based on the mass fractions of raw materials, it includes: 65-70 parts nylon resin, 25-30 parts glass fiber, 10-15 parts maleic anhydride-grafted C9 petroleum resin, 0.8-2.3 parts composite lubricant, and 3-6 parts glass microspheres. The composite lubricant consists of 0.3-0.8 parts stearamide and 0.5-1.5 parts silicone powder.

3. The high-gloss, high-surface-energy nylon composite material according to claim 2, characterized in that: The maleic anhydride grafting rate of the C9 petroleum resin is 1.5-3.5 wt%.

4. The high-gloss, high-surface-energy nylon composite material according to claim 3, characterized in that: The method for preparing maleic anhydride-grafted C9 petroleum resin includes the following steps. Maleic anhydride-grafted C9 petroleum resin was prepared by melt grafting C9 petroleum resin and maleic anhydride. The extrusion temperature for melt grafting is 160-230℃, and the amount of maleic anhydride added is 2-5 wt% of C9 petroleum resin based on the mass fraction of C9 petroleum resin.

5. The high-gloss, high-surface-energy nylon composite material according to claim 1, characterized in that: The nylon resin is selected from one or more of PA6 resin and PA66 resin.

6. The high-gloss, high-surface-energy nylon composite material according to claim 1, characterized in that: The average diameter of the glass fiber is 10-50 μm.

7. The high-gloss, high-surface-energy nylon composite material according to claim 1, characterized in that: The glass microspheres are solid glass microspheres modified with silane coupling agent, with a particle size of 20-30 μm.

8. The high-gloss, high-surface-energy nylon composite material according to claim 1, characterized in that: The raw materials also include 0.2-1 parts of other additives, which are antioxidants, by mass percentage.

9. A method for preparing a high-gloss, high-surface-energy nylon composite material according to any one of claims 1 to 8, characterized in that: include, According to any of the proportions described in claims 1 to 8, the components other than glass fiber are highly mixed and fed into a twin-screw extruder through the main feed port, and the glass fiber is fed into the twin-screw extruder through the side feed port. After melt blending, extrusion and pelletizing, a high-gloss high-surface-energy nylon composite material is obtained. The extrusion temperature is 240-280℃, and the screw speed is 280-300 rpm.

10. The application of the high-gloss, high-surface-energy nylon composite material according to any one of claims 1 to 8 in the preparation of automotive interior parts, electronic product housings, and packaging containers.